2023
DOI: 10.1590/s1677-5538.ibju.2023.0065
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oncological and surgical outcomes after Video Endoscopic Inguinal Lymphadenectomy (VEIL) in patients with penile cancer

Abstract: Objective: To report outcomes from the largest multicenter series of penile cancer patients undergoing video endoscopic inguinal lymphadenectomy (VEIL). Materials and Methods: Retrospective multicenter analysis. Authors of 21 centers from the Penile Cancer Collaborative Coalition-Latin America (PeC-LA) were included. All centers performed the procedure following the same previously described standardized technique. Inclusion criteria included penile cancer patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The objective of ILND for individuals with PeCa is to obtain precise local staging, provide guidance for adjuvant treatment choices, and enhance overall survival rates. ILND is the gold-standard treatment for inguinal node-positive patients, and its staging role has been refined in cN0 disease after the introduction of DSNB [1,9,12]. Nevertheless, ILND continues to play a role in this setting since false negative cases after a DSNB are still an issue while its availability is scarce [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of ILND for individuals with PeCa is to obtain precise local staging, provide guidance for adjuvant treatment choices, and enhance overall survival rates. ILND is the gold-standard treatment for inguinal node-positive patients, and its staging role has been refined in cN0 disease after the introduction of DSNB [1,9,12]. Nevertheless, ILND continues to play a role in this setting since false negative cases after a DSNB are still an issue while its availability is scarce [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although OILND has been demonstrated to be an effective procedure, the significant associated morbidity has been a considerable burden for both surgeons and patients. In this regard, the minimally invasive approach as laparoscopic (VEIL) or robotic (RA-VEIL) has been proven to reduce postoperative morbidity while maintaining the oncological efficacy [7][8][9]. Furthermore, a simultaneous approach has been proposed for both staging and treatment purposes in patients elected for bilateral invasive inguinal node assessment to further decrease surgery-related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Tobias-Machado and collegues from Brazil performed in page 580 ( 3 ) a nice study about the long-term oncological and surgical outcomes after Video Endoscopic Inguinal Lymphadenectomy (VEIL) in patients with penile cancer and concluded that VEIL seems to offer appropriate long term oncological control with minimal morbidity. In the absence of non-invasive stratification measures such as dynamic sentinel node biopsy, VEIL emerged as the alternative for the management of non- bulky lymph nodes in penile cancer.…”
mentioning
confidence: 99%